Prospective, Multicenter Feasibility Study to Evaluate Differential Target Multiplexed Spinal Cord Stimulation Programming in Subjects With Chronic Intractable Back Pain With or Without Leg Pain. Issue 7 (2nd June 2020) - Fishman, Michael A.; Calodney, Aaron; Kim, Philip; Slezak, Jan; Benyamin, Ramsin; Rehman, Atiq; Soto, Eliezer; Yang, Thomas; Hacobian, Asteghik; Griffith, Lee; Yu, Cong; Vallejo, Ricardo
Abstract: Objective: This prospective, open‐label, multicenter study evaluated the feasibility of spinal cord stimulation (SCS) therapy programming for chronic low back pain that uses multiple electrical pulsed signals (Differential Target Multiplexed). Methods: Twenty‐five SCS candidates with low back pain equal to or greater than lower limb pain were enrolled at 7 sites in the United States. The subjects evaluated standard and Differential Target Multiplexed programs, each for 4 ± 1 days. A commercially available SCS trial system was used for standard SCS therapy programming. During the trialing of the multiplexed programs, implanted temporary leads were connected to an investigational external trial stimulator system. Results: Twenty subjects concluded the study. The mean baseline numeric pain rating scale (NPRS) score for low back pain was 7.4, with a mean age of 62.4 years and mean pain duration of 18.0 years. Significant relief in back pain was observed for both treatments, with significantly better response with multiplexed programming. At the end of the trial period, subjects reported a reduction in their mean NPRS score from baseline to 4.2 after standard programming and to 2.4 after Differential Target Multiplexed programming. The difference between standard and multiplexed programming was significant. The responder rate for low back pain relief was 50% for standard programming and 80% for Differential Target Multiplexed programming. Eighty‐five percent of subjects who evaluated both programming approaches preferred Differential Target Multiplexed SCS. Conclusion: In this difficult‐to‐treat patient population, subjects reported significant reduction in chronic back pain when using multiplexed programming. A randomized clinical trial is needed to confirm the results from this feasibility study.